1987
DOI: 10.1111/j.1471-4159.1987.tb13137.x
|View full text |Cite
|
Sign up to set email alerts
|

Destinations of Some Fast‐Transported Proteins in Sensory Neurons of Bullfrog Sciatic Nerve

Abstract: Many characteristics of proteins that are fast axonally transported have been described, but the destinations of most within the neuron remain unknown. We have studied the destinations of some fast-transported proteins in sensory neurons of the bullfrog sciatic nerve, specifically to determine which may be deposited in axons and which may be destined for more distal, possibly terminal, areas. Dorsal root ganglia were pulse-labeled with [35S]methionine in vitro, following which they were separated from the scia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Several previous studies have dealt with quantitative alterations in fast transported proteins after amphibian sciatic nerve injury (Perry and Wilson, 198 1;Tedeschi and Wilson, 1983;Perry eta]., 1987b;Rulli and Wilson, 1987;Edbladh et al, 1990;Edstrom et al, 1990). In common with these, the present results suggest the absence of dramatic quantitative changes of proteins in such nerves.…”
Section: Discussionsupporting
confidence: 81%
“…Several previous studies have dealt with quantitative alterations in fast transported proteins after amphibian sciatic nerve injury (Perry and Wilson, 198 1;Tedeschi and Wilson, 1983;Perry eta]., 1987b;Rulli and Wilson, 1987;Edbladh et al, 1990;Edstrom et al, 1990). In common with these, the present results suggest the absence of dramatic quantitative changes of proteins in such nerves.…”
Section: Discussionsupporting
confidence: 81%
“…The first two possible explanations relate to the fact that axonally transported macromolecules must be unloaded from the transport vector when they reach their appropriate destinations. It is known that different axonally transported proteins have different sites of deposition within neurons (e.g., Goodrum and Morell, 1982;Toews et al, 1982;Stone et al, 1984;Rulli and Wilson, 1987) and differences in the degree of unloading of different classes of transported lipids have also been demonstrated (Blaker et al, 1981;Toews et al, 1983Toews et al, , 1988Droz et al, 1985). Our present findings of attenuation of the crest of rapidly transported glycoproteins and a decrease in the amount of labeled glycoproteins cleared from the axons, suggest that acrylamide treatment brings about an increase in the unloading or deposition of axonally transported glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…We have designated these as class III FT proteins. Quantitative analyses have shown that the longer the length of axon, the greater the percentage of fasttransported proteins destined for axon deposition (Grafstein, 1967;Rulli and Wilson, 1987;Cancalon andBeidler, 1975, 1977). How do members of the class III FT proteins localize predominantly to axons?…”
Section: Discussionmentioning
confidence: 99%
“…This presumption has been supported by experimental investigations demonstrating selective localization of some rapid axonally transported proteins to axons or terminals (for review see Smith and Snyder, 1992). Specifically, some rapidly transported proteins have been found to translocate preferentially as moving phase species (presumably destined for terminals) while other rapidly transported proteins have been found to enter a relatively stationary phase (presumably destined for deposition in axons) (Cancalon andBeidler, 1975, 1977;Stone et al, 1984;Rulli and Wilson, 1987;Li et al, 1996a,b). Quantitative analyses have suggested that the longer the length of the axon, the greater the percentage of fast-transported proteins destined for axon deposition (Grafstein, 1967;Rulli and Wilson, 1987;Cancalon andBeidler, 1975, 1977).…”
mentioning
confidence: 92%
See 1 more Smart Citation